FIRE PREVENTION MEASURES IN UZBEKISTAN - Saboxon Umarova Minavvarovna; Parpiyeva Ziyoda Sherzodjon qizi, Tursunova Saodatxon Hamdamali qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Fire is an uncontrollable phenomenon, a disaster that destroys priceless material and cultural assets every minute, especially it is an emergency situation that causes hardship to the lives of citizens.